Health education and nutritional diet-based mentoring in an effort to control excess fat intake - Mudlikah, Siti; Suprapti, Suprapti; Agnesia, Dian; Arifah, Dwi Fitriyatul; Shoihah, Khilyatus (Universitas Muhammadiyah Magelang, 2021)
Excess fat intake causes the accumulation of body fat which results in obesity. The high cholesterol levels cause health problems and the reproductive system of women of childbearing age. Excess fat intake is influenced by several factors such as a lack of understanding of the consumption of nutritious and healthy foods, and the impact of excess fat intake on the risk of obesity, high cholesterol and menstrual cycle disorders. The purpose of this service activity is to control excess fat intake, obesity, high cholesterol levels, and regularity of the menstrual cycle of women of childbearing age. The methods used in this service activity include health education seminars, screening for obesity, cholesterol levels, and regularity of the menstrual cycle and nutritional diet-based mentoring. After the service activities, it was found that there was an increase in understanding about excess fat intake, obesity, high cholesterol and the menstrual cycle. Then, there are changes with the achievement of normal weight, normal cholesterol levels and regular menstrual cycles in women of childbearing age.